Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.607200
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic constraints on English stress timing

Abstract: The evidence for isochrony of stress timing is weak at best for ordinary prose, but this does not mean that the timing of stresses is always unaffected by global constraints. We asked subjects to continually repeat the phrase Take a pack of cards and to temporally align the words take and cards with an auditorily presented stimulus consisting of just the words take and cards repeated several times. The phase of the cards stimulus relative to a reference cycle defined by the take-take interval was varied over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(138 citation statements)
references
References 16 publications
(4 reference statements)
4
134
0
Order By: Relevance
“…Both Allen (1972) and Morton et al (1976) found that the perceived beat of a syllable was located near the onset of voicing of the vowel in the stressed syllable. However, perception of the beat is pushed earlier as a function of the length of the preceding onset consonant cluster (the longer the cluster, the earlier the percept of the beat), and later as a function of the length of the syllable coda (Cummins & Port, 1998). The measure applied here-the temporal distance between the vowel onsets in disyllabic words-we call durVonVon (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Both Allen (1972) and Morton et al (1976) found that the perceived beat of a syllable was located near the onset of voicing of the vowel in the stressed syllable. However, perception of the beat is pushed earlier as a function of the length of the preceding onset consonant cluster (the longer the cluster, the earlier the percept of the beat), and later as a function of the length of the syllable coda (Cummins & Port, 1998). The measure applied here-the temporal distance between the vowel onsets in disyllabic words-we call durVonVon (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Coupled oscillator models of speech rhythm (Barbosa 2006(Barbosa , 2007O'Dell and Nieminen 2009) usually utilise at least two universal oscillators, the syllabic oscillator and the phrase stress oscillator, that operate at distinct timescales (cf. Cummins and Port 1998;Tilsen 2009). The 'task' of the syllabic oscillator is to keep pace with the vowel onset sequence.…”
Section: Prosodic Annotation and Methodsmentioning
confidence: 99%
“…Speech is fundamentally rhythmic in nature, if not in the sense of strict periodicity (Cummins & Port, 1998). The temporal complexity of speech production makes the question of coordination all the more challenging and interesting.…”
Section: Interarticulatory Coordination In Speechmentioning
confidence: 99%